Reconciling the Divergent Findings from Clinical Trials and Observational Studies of Menopausal Hormone Therapy for Prevention of Coronary Heart Disease - Rossouw, Jacques E. (Seminars in Reproductive Medicine, 2014)
In the Women's Health Initiative (WHI) observational study, current use of estrogen plus progestin therapy (EPT) and estrogen therapy showed an association with reduced risk of coronary heart disease (CHD). However, after taking into account the early increase in risk, the observational study and clinical trial hazard ratios did not differ significantly and showed no benefit for CHD. These findings were confirmed in novel reanalyses for EPT use in the Nurses' Health Study which for the first time included early events and yielded results similar to those of the WHI trial in showing no CHD benefit. The underestimation of CHD risk in observational studies of menopausal hormone therapy appears to lie in their inefficiency at capturing the early increase in risk in current users; by contrast clinical trials are very efficient at capturing early risk. Observational study data mostly reflects long-term use in women who survive the early increase, while trials mainly reflect short-term use. Confounding plays a role, but biologic differences in study populations are unlikely to explain the different risk estimates.
Keywords: estrogen; progestin; coronary heart disease; epidemiology; clinical trials